The anxiety levels, quality of sleep and life and problem-solving skills in healthcare workers employed in COVID-19 services - Korkmaz, Sevda; Kazgan, Aslı; Çekiç, Sevler; Tartar, Ayşe Sağmak; Balcı, Hale Nur; Atmaca, Murad (Journal of clinical neuroscience, 2020)
•Coronavirus-2 pandemic physically and mentally affects healthcare workers.•Healthcare workers might develop psychiatric symptoms such as anxiety and sleep disturbance.•Psychiatric symptoms could adversely affect the problem-solving skills of healthcare workers and cause a deterioration in their quality of life. The present study aims to investigate the level of anxiety experienced by healthcare workers employed in COVID-19 services, the effects of anxiety on sleep quality and quality of life and, the relationship between these variables and problem-solving skills of the healthcare workers. The study was conducted in two healthcare facilities which serve as pandemic hospitals. 140 healthcare workers, who were employed in the COVID-19 outpatient clinics or emergency departments, participated in the present study. All participants were submitted to the Pittsburgh Sleep Quality Index (PSQI), Problem Solving Inventory (PSI), World Health Organization Quality of Life-BREF (WHOQOL-BREF), Beck Anxiety Inventory (BAI). The number of participants without anxiety was 41(29%), with mild anxiety was 53(38%). Clinically significant anxiety findings were found in only 33% of the participants. A positive correlation was found between the participants’ BAI scores and PSQI, PSI scores, and a negative correlation with the WHOQOL-BREF scores. PSQI and PSI scores of nurses were statistically higher when compared to those of physicians and staff. WHOQOL-BREF scores were found to be lower. Healthcare workers might develop psychiatric symptoms such as anxiety and sleep disturbance. Such symptoms could adversely affect the problem-solving skills of healthcare workers and cause a deterioration in their quality of life.